Sistem Manajemen Energi Listrik dan Otomatisasi pada Kolam Ikan - Pambudi, Wahyu Setyo; Ath thuur, Januar Adiyansyah; Amalia, Devi; Munir, Misbahul (Institut Teknologi Adhi Tama Surabaya, 2025)
Indonesia has abundant fishery resources, including tilapia (Oreochromis niloticus), a leading commodity in freshwater fisheries. With increasing market demand locally and internationally, fish farmers must control water use and production costs more efficiently by intensive cultivation with Recirculating Aquaculture Systems (RAS). However, a significant challenge in RAS systems is the high operational cost, particularly the electrical energy consumption for pumps and aerators. The research aimed to implement energy management in RAS-based tilapia aquaculture by utilizing real-time electricity monitoring technology, ON-OFF control automation, and Variable Speed Drive (VSD) inverters. The researcher conducted tests on two conventional and intensive systems. The intensive system used a control strategy that integrates scheduling on timer outlets and pump speed control through inverters. The test results showed that the intensive system was more efficient than the conventional system, with an initial power consumption of 80.75 kWh, then decreasing to 67.97 kWh. The energy efficiency reached 16%, equivalent to a monthly cost saving of Rp17,279, making the total operational cost of the intensive system only Rp91,895 per month. In addition, the Blynk app-based control system enabled real-time energy monitoring and management, supporting energy savings and improved cost efficiency.